The Growth of Launaea taraxacifolia (Asteraceae) and its Response to Shading - Sakpere, A. M. A.; Aremu, O. A. (2014)
Some baseline information on the growth of Launacea taraxacifolia (Wild) Amin Ex. C. Jeffrey was gathered. Rhizomes sprouted within 10 days. The sprouted rosettes bolts in about 56 Days After Planting (DAP) and seeds are formed in about 70 - 75 DAP. There was only 17% branching in the shoot. Number of flowering branches and number of buds on each flowering branch among other reproductive parameters were observed. Differences were observed in the habit and growth of L. taraxacifolia grown in the open and under shade. All growth parameters, except plant height, were significantly reduced by shading (although this was reversed during the flowering stage). Plants in the shade did not flower at all. Nutritionally, L. taraxacifolia was observed to be a good source of mineral elements like Phosphorus and Iron. It also contains some protein. The best time for the harvest appears to be between the 6th and 8th weeks after planting.